Cognitive Behavioral Therapy for Late-Life Depression: Evidence, Issues, and Recommendations. Issue 1 (February 2022) - Bilbrey, Ann Choryan; Laidlaw, Kenneth; Cassidy-Eagle, Erin; Thompson, Larry W.; Gallagher-Thompson, Dolores
Abstract: This paper discusses relevant research on structured therapy techniques used in the course of cognitive behavioral therapy (CBT) that are helpful in treating older adults with depressive disorders. These findings are compared and contrasted with clinical observations pertinent to the identification of moderator/mediator and other contextual factors critical to the efficacy of CBT for the treatment of this population. While some of these techniques may be viewed as a specific type of intervention in their own right (e.g., Behavioral Activation and Lifeskills Approach), their underlying theory and specific operations are consistent with the underpinnings of other cognitive and behavioral strategies and may be frequently juxtaposed within a CBT framework, depending on the nature of the problem and the specific available resources. Several common issues identified as being problematic for clinicians new to clinical work with older adults are highlighted, and useful information on how to adapt/modify traditional CBT approaches to augment treatment outcome with older adults is provided. Clinicians who use CBT will be familiar with most components discussed, but one novel augmentation towards the development of an age-appropriate format of CBT, termed Lifeskills Approach, is included. In this approach, clinicians are encouraged to identify and incorporate evidence of prior successful coping strategies to challenges that occur across the lifespan. This approach values and respects how clients have overcome aversive life experiences to facilitate attentional deployment away from a narrative of failure to one of resilience and self-acceptance, thereby down-regulating emotional distress. An important consideration discussed is how to use behavioral activation effectively, particularly with persons who have mild cognitive impairment (MCI) or are in the early stages of dementia. Highlights: CBT is an effective treatment for older adults with various types of depressive disorders. A number of specific recommendations to enhance effectiveness of CBT with older adults are provided. Behavioral activation is described in detail and recommended as an excellent starting point for CBT with depressed older adults. Cognitive reappraisal, when appropriate, may help prevent future depressive episodes and may be associated with longer-term maintenance of gains. A novel approach involving recognition and application of Lifeskills is presented. Although there is a solid research base on the efficacy of CBT for late life depression, several topics for needed research in the future are delineated.